Dietary mannan oligosaccharide enhances growth and survival of juvenile tiger shrimp Penaeus monodon against experimental challenge with Vibrio harveyi and white spot syndrome virus - Felix, N.; Arasi, P. Kalaimani; Manikandan, K. (Indian Journal of Fisheries, 2020)
A 45-days feeding trial was conducted on juvenile tiger shrimps Penaeus monodon of size 0.997Â±0.098 g with diets containing Mannan oligosaccharides (Mos) at three graded levels (0.1, 0.2 and 0.3%). Maximum weight gain (1.353 g) was achieved in shrimps fed with 0.3% Mos concentration, followed by 0.2% Mos (1.224 g). Best feed conversion ratio (FCR) of 2.406 was registered in 0.3% Mos groups. Results indicate that there was a significant difference (p